Examining Lesson Quality: An In-Depth Analysis of STEM-based Lesson Design Crafted by Preservice Elementary Teachers - Fitri Nuraeni; Hafiziani Eka Putri; Nenden Permas Hikmatunisa; Rissa Puspita Sari; Afridha Laily Alindra; Hun Ravy (Journal of Innovation in Educational and Cultural Research, 2024)
Due to its significance in fostering 21st-century skills, Science, Technology, Engineering, and Mathematics (STEM) education has rapidly evolved across the country. However, designing effective and meaningful STEM-based lessons is still challenging, especially at the elementary school level. Thus, future elementary teachers should be trained to develop integrated STEM-based lesson plans. This research aims to explore the quality of STEM-based lessons designed by pre-service elementary teachers. This study analyzed six STEM-based lesson plans created by 32 preservice elementary teachers as a final group project in the STEM Learning in Elementary School course. Employing a descriptive analysis method, the study evaluated the lesson plans using STEM Integration Curriculum Assessment (STEM-ICA) indicators to shed light on the lesson design quality. Findings reveal varying scores across STEM-ICA indicators, emphasizing ideal science integration but indicating room for improvement in mathematics integration within the lesson. Assessment alignment and the need for stronger connections in engineering design activities are highlighted. This contributes to discussions on enhancing preparation programs for high-quality STEM educators in elementary schools.